2018
DOI: 10.1101/cshperspect.a030528
|View full text |Cite
|
Sign up to set email alerts
|

Genetically Engineered Mouse Models of Prostate Cancer in the Postgenomic Era

Abstract: Recent genomic sequencing analyses have unveiled the spectrum of genomic alterations that occur in primary and advanced prostate cancer, raising the question of whether the corresponding genes are functionally relevant for prostate tumorigenesis, and whether such functions are associated with particular disease stages. In this review, we describe genetically engineered mouse models (GEMMs) of prostate cancer, focusing on those that model genomic alterations known to occur in human prostate cancer. We consider … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 168 publications
(229 reference statements)
1
32
0
Order By: Relevance
“…Bone is the predominant site of metastasis in this disease, although a subset of highly aggressive PCa disseminates to the lung and soft tissues (Arriaga and Abate-Shen, 2019). The biology of lethal metastatic PCa is poorly understood, and there are few murine models to date that recapitulate this pattern of aggressiveness (Arriaga and Abate-Shen, 2019). Our study provides the field with an invaluable model to study the process of PCa dissemination in an immune-competent and tissue-specific context.…”
Section: Resultsmentioning
confidence: 99%
“…Bone is the predominant site of metastasis in this disease, although a subset of highly aggressive PCa disseminates to the lung and soft tissues (Arriaga and Abate-Shen, 2019). The biology of lethal metastatic PCa is poorly understood, and there are few murine models to date that recapitulate this pattern of aggressiveness (Arriaga and Abate-Shen, 2019). Our study provides the field with an invaluable model to study the process of PCa dissemination in an immune-competent and tissue-specific context.…”
Section: Resultsmentioning
confidence: 99%
“…In almost half of patients with prostate cancer, the tumor carries one of recurrent translocations that place one of the genes from the ETS family (ERG, ETV1, ETV4, ETV5, FLI1) downstream to the promoter of a gene active in the prostate, with consequent aberrant overexpression of the respective ETS gene [2][3][4][5]. The role of the ETS genes in prostate carcinogenesis has been investigated in transgenic mice models with a prostate-specific ETS overexpression [6,7]. The results have not been always concordant: some studies suggest that ERG or ETV1 overexpression promotes premalignant in situ lesions (equivalent to prostatic intraepithelial neoplasia, PIN) [8][9][10][11][12], whereas other studies suggest that this overexpression is not sufficient to cause the onset of cancer [13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple lines of evidence in the literature have indicated that PTEN plays a haploinsufficient tumor-suppressive role. Transgenic mouse models have shown that PTEN haploinsufficiency or heterozygosity in mouse prostate epithelium can cause prostate lesions, whereas homozygous PTEN deletion causes prostate carcinoma [ 20 , 23 , 94 ]. Moreover, PTEN loss has been shown to cooperate with other oncogenic events to accelerate prostate cancer progression in vivo in a dose-dependent manner, and heterozygous loss of PTEN has been shown to accelerate prostate cancer progression in some clinical datasets [ 22 , 76 , 79 , 95 , 96 , 97 ].…”
Section: Targeting Pten-deficient Prostate Cancermentioning
confidence: 99%